Insights on the acid hydrolysis of achira (Canna edulis) starch: Crystalline and double-helical structure changes impacting functionality. (January 2022) - Mendez-Montealvo, Guadalupe; Velazquez, Gonzalo; Fonseca-Florido, Heidi A.; Morales-Sanchez, Eduardo; Soler, Adrian
Abstract: In this study, achira ( Canna edulis ) starch (AS), a non-conventional starch, was hydrolyzed using hydrochloric acid (7.5%) from 3 to 15 days to investigate the effect of long term acid hydrolysis on the evolution of the crystalline and double-helical structure changes, and its repercussion on the functionality. After 15 days, the degree of hydrolysis was 40.3 ± 0.8%. Micrographs revealed the granular structure loss after 6 days of hydrolysis. Acid hydrolysis decreased the crystallinity from 36.6 to 21.1% after 3 days but it increased to 27.0% after 15 days, while the degree of double helix and degree of order decreased after the acid treatment. Structural degradation of AS induced by the acid hydrolysis was reflected in the significant reduction of the enthalpy change of gelatinization and swelling, and the significant increase of the water solubility and water holding capacity, reaching maximum values at 9 (52.6 ± 1.0%) and 15 (266.4 ± 0.4%) days, respectively. Through the appropriate modification of the crystalline and double-helical structure by acid hydrolysis, the AS functionality can be regulated by adjusting the hydrolysis time, expanding the use of AS in the food industry. Graphical abstract: Image 1 Highlights: The amount and packing density of double helices decreased after acid hydrolysis. Disassembled double-helices were rearranged into more crystalline structures. The highest water solubility value (52.6 ± 1.0%) was achieved after 9 days. Maximum water holding capacity (266.4 ± 0.4%) was obtained after 15 days.